Characterization of mohair and cashmere in regions of Kazakhstan, Kyrgyzstan and Uzbekistan - Iñiguez, Luis; Mueller, Joaquin Pablo; Ombayev, A.; Aryngaziyev, S.; Ajibekov, A.; Yusupov, S.; Ibragimov, A.; Suleimenov, M.; El-Dine Hilali, M. (2017)
To generate information on animal fiber quality traits in Central Asia, as a prelude to genetic improvement, fiber samples of 495 cashmere goats from Kazakhstan and Uzbekistan, and 448 mohair goats from these two countries and Kyrgyzstan were characterized. Fixed effects involved location (geographical), animal age and coat color. Fiber traits included greasy down yield for cashmere (GDY, %) and clean yield (CY, %) for mohair; mean down diameter (MDD, μm) for cashmere and mean fiber diameter (MFD, μm) for mohair; coefficient of variation (CV, %) associated with MFD or MDD; comfort factor (CF, %); fiber curvature (Curv,°/mm) and staple length (SL, mm). Percentages of med, kemp and total medullation (TM) were also obtained for mohair samples. Residual phenotypic correlations between traits were calculated. Cashmere GDY, MDD, CV, CF, Curv and SL averaged respectively 26.8 ± 0.6%, 17.2 ± 0.1 μm, 21.0 ± 0.2%, 98.9 ± 0.2% 69.7 ± 0.5°/mm and 29.4 ± 0.7 mm. Location was a significant differentiating factor for all cashmere traits. Significant GDY decrease and MDD increase was observed with age. The SL was highly correlated with GDY, MDD and CF (0.63, 0.65 and −0.64, respectively), and so was GDY with MDD (0.78). Mohair CY, MFD, CV, CF, Curv and SL averaged respectively 76.7 ± 0.3%, 29.3 ± 0.2 μm, 29.5 ± 0.2%, 60.5 ± 1.0%, 48.5 ± 0.2°/mm, and 176.9 ± 1.9 mm, whereas med, kemp and TM averaged respectively 5.7 ± 0.3, 5.5 ± 0.3 and 11.2 ± 0.6%. Significant location differences were found for mohair CY, MFD, CF, Curv, SL, kemp and TM, along with a significant MFD increase and CF decrease with age. All variables, except CY, differentiated according to coat colors. CY was highly correlated with MFD (0.70), SL (0.80), CF (−0.72), Curv (−0.81) and kemp (−0.70). The mohair MFD was also highly correlated with CF (−0.99), Curv (−0.81), SL (0.70) and FM (0.64). The study detected important variability for fiber quality traits in view of (1) heterogeneity for all studied cashmere traits, except for CF, and in all studied mohair traits, and (2) significant location differences for most important quality traits in cashmere and mohair. This suggests that a good base for fiber quality improvement is in place in the region